O HOMEM E SEUS DUPLOS: A REFLEXIVIDADE DO SUJEITO NA POESIA DE ROBERVAL PEREYR - Moreira, Idmar Boaventura (2007)
The concept of subject, as it was defined in modernity (atomistic and centered in the reason), especially from Enlightenment, goes bankrupt in modernity crisis, on the point of, in last decades, many thinkers amongst them the postmodern ones commending his death, together with modernity death. However, it is possible to find a compromise between the monolithic subject of illuminist modernity and the schizophrenic subject of postmodernity: the reflexive subject of high modernity. Such concept points to a definition of lyric subject as an opening for the otherness, that it only becomes possible in a phenomenological conception of the lyric experience, which author, reader and poem dissolve their being in the being of the language. Roberval Pereyr s poetical workmanship, in its turn, points to the question of the subject when it dramatizes his fight for survival. It does that assuming the formal and thematic fragmentation, defying the established reason and appealing for the unconscious strata of the nature human. His poetry is an ego negation, at the same time it is the controller of individual potentialities and controlled by external forces; it is the narrative of a subject walk in search of an origin, a face and an identity, always constructed from the meeting with other, in a posture which discloses the subject reflexive attitude in the construction of a coherent history of itself; finally, it is the assumption of the poetry as way the only one, maybe of full accomplishment of the subjectivity.